LUDNOŚĆ W WIEKU POPRODUKCYJNYM W STRUKTURACH GOSPODARSTW DOMOWYCH W POLSCE - Roeske-Słomka, Iwona (Wydział Prawa i Administracji UAM, 1999)
Data from 1996 all-Poland studies on households budgets are the basis for empirical analyse of the participation of persons aged 65 and more within the structures of households. In 1996 the number of population aged 65 and more amounted to 4.426 thousands, i.e. about 10 per cent of the entire population (share of women was up to 6 per cent). From the point of view of a kind of household the biggest share of the aged 65 and more was, obviously, in households belonging to the retired (almost 32 per cent) and then - in the farmers households (near 10 per cent), next - a bit less, o f about 7 per cent, in households of workers being users of a farm. The share of post-productive population in the so-called households of the employees is of about 2 per cent (and only 0,5 per cent of this number are the men).
POPULATION IN POST-PRODUCTIVE AGE WITHIN THE STRUCTURES OF HOUSEHOLDS IN POLAND